1995
DOI: 10.1111/j.1096-3642.1995.tb00119.x
|View full text |Cite
|
Sign up to set email alerts
|

The postcranial skeleton of the Devonian tetrapod Tulerpeton curtum Lebedev

Abstract: Postcranial remains of the Russian Late Devonian tetrapod Tulerpeton include the hexadactylous fore limb, hind limb, anocleithral pectoral girdle, squamation, and associated disarticulated postcranial bones. A cladistic analysis indicates that Tulerpeton is a reptiliomorph stem‐group amniote and the earliest known crown‐group tetrapod: Acanthostega and Ichthyostega are successively more derived plesion stem‐group tetrapods and do not consititute a monophyletic ichthyostegalian radiation. Previous analyses sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
137
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(141 citation statements)
references
References 48 publications
2
137
1
1
Order By: Relevance
“…9H) (Coates, 1996). A similar configuration is described in other stem tetrapods such as Baphetes (Milner & Lindsay, 1998), Crassigyrinus and Ichthyostega (Panchen, 1985), Greererpeton (Godfrey, 1989), and Tulerpeton (Lebedev & Coates, 1995).…”
Section: (C) Stem Tetrapodsmentioning
confidence: 69%
See 1 more Smart Citation
“…9H) (Coates, 1996). A similar configuration is described in other stem tetrapods such as Baphetes (Milner & Lindsay, 1998), Crassigyrinus and Ichthyostega (Panchen, 1985), Greererpeton (Godfrey, 1989), and Tulerpeton (Lebedev & Coates, 1995).…”
Section: (C) Stem Tetrapodsmentioning
confidence: 69%
“…8F). In Tulerpeton, a rugose area above the glenoid was suggested as the origin of the subcoracoscapularis, and tubercles were noted on the posterior edge of the clavicle (Lebedev & Coates, 1995). In Hynerpeton, rugose ridges thought to be muscle scars were described on the dorsal border of the subscapular fossa (Daeschler et al, 1994).…”
Section: (C) Stem Tetrapodsmentioning
confidence: 99%
“…Given its more basal cladistic position compared to Ichthyostega and all later tetrapods, the anatomy of both the limbs and the gills of Acanthostega led to the proposal that the tetrapod limb originally evolved as a specialised organ for aquatic locomotion. Indeed, Coates and Clack (1995) suggested that the whole Devonian tetrapod radiation including not only Acanthostega, but also Ichthyostega and the possible basal amniote Tulerpeton (Lebedev and Coates 1995) were entirely aquatic animals. Support for this idea has recently come from the discovery that Ichthyostega does in fact also possess gill bars, and has a unique ear structure designed for hearing under water rather than in air (Clack et al 2003).…”
Section: The Vertebrate Conquest Of Land: Origin Of the Amniotamentioning
confidence: 99%
“…Tulerpeton (Lebedev and Coates 1995), which, if correctly interpreted, indicates that the living Amniota must have separated from their closest living relatives, the Amphibia, at least 360 Ma. If Tulerpeton is rejected, the next candidate for earliest stem-amniote is the 333 Ma Lower Carboniferous Westlothiana ( Fig.…”
Section: The Vertebrate Conquest Of Land: Origin Of the Amniotamentioning
confidence: 99%
“…Given that separate olfactory and vomeronasal systems are present in amphibians and in amniotes, the vomeronasal system must have been present in the last common ancestor of these two groups, and this animal is now thought to have been fully aquatic (Panchen, 1991;Lebedev and Coates, 1995). An understanding of the function of the vomeronasal system in aquatic amphibians may help shed light on the factors that led to the evolutionary origin of the vomeronasal system.…”
Section: Discussionmentioning
confidence: 99%